Strengthening of reinforced concrete deep beams having large square openings in shear zone with carbon fiber reinforced polymer (CFRP) wrap - Ng, Kin Mun (2015)
Typically, the reinforced concrete (RC) deep beam with large openings are facing some severe problems such as the interruption of natural load transfer by concrete struts acting in compression which can cause an intensive reduction in strength; and the clearly visible cracks in serviceability conditions. The CFRP has become an alternative solution to this issue and being extensively used as an external reinforcement to resolve the strength requirements in structural systems due to extremely strong yet light weight, outstanding fatigue properties, excellent corrosion resistance and easy yet efficient application on concrete. This experimental study is focuses on the investigation of the effect of CFRP wrap in strengthening RC deep beams with large square openings located in shear zone. Three approaches are under consideration; the first is the determination of natural load transfer in normal deep beam without opening, the second is the large square openings in deep beam without CFRP strengthening, and the third is the large square openings in deep beam with CFRP attached around the openings. A total of four RC deep beams which included a solid RC control beam, a deep beam with two large square openings, and two beams with two large square openings strengthened by using CFRP strips in different strengthening configurations, were tested to failure under four point loading to determine the relative structural behaviour such as ultimate load, failure mode, crack patterns, and load deflection behaviour. All RC deep beams were designed in a dimension of 120 x 600 mm and 2400 mm in length. The width and height of large square openings were in a dimension of 270 x 270 mm and located 300 mm from the edge of the deep beam. The loading point and support were located at 800 mm and 300 mm from the edge of the deep beam, respectively. RC deep beam with large square openings, US-BSO was significantly reduced the beam capacity by 61.76 % as compared to solid control beam, CB. However, the RC deep beam with large square openings strengthened by CFRP strips wrapped in U-shaped, SU-BSO has increases the beam capacity by 62.77 % compared to US-BSO. From the results obtained, it was found that the most effective CFRP strengthening method for RC deep beam with large square openings was U-shaped, which recovered the beam capacity up to 62.24 % as compared to solid control beam